OPTIMALISASI HASIL BELAJAR DAN AKTIVITAS BELAJAR SISWA MELALUI PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI SISTEM DIGESTI MANUSIA BERVISI SETS - Minarti, Ipah Budi (BIOMA, 2015)
This study aimed to develop learning tools in the topic of humandigestion system vision SETS. SETS approach was an integratedlearning which is expected to exercise students to have the ability tolook at things in an integrated manner by taking into the fourelements, namely science, environment, technology, and society. Thisresearch was Research and Development with the subject was studentsof SMP 1 Kudus grade VIII that follows extracurricular YouthScientific Work consisting of 10 students for limited scale test and 3classes for wide scale test with purposive sampling. The resultsshowed that the learning tools were declared valid by expert. Learningtools was effectively used in learning, because > 80% of studentsreached minimal standard qualification and there was an increase inthe value of pretest-posttest. Learning activities of students of thethree experimental class >75% achieving an active and very activecategories.Keywords: learning activities, learning outcomes, learning tools,SETS.